Solve the brackets, starting from the innermost and working outwards:
2(7x+y(-3(5x-2y)))
multiply by -3: 2(7x+y(-15x+6y))
multiply by y: 2(7x - 15xy+6y2)
multiply by 2: 14x - 30xy + 12y2
I suspect, though, that there is something missing before the -3.
-7x + 6 + 7x - 2 = 4
x2+7x+12
2y + 7x + y-1?
7x + y = 4y = 4 - 7x
7x + 2 = 5,6
Subtract by 7x and divide by 2.
7x + 51x + 14= 58x + 14= 2(29x + 7)
You need to solve x before I can answer this
7x + y = 8 Subtract 7x from each side of the equation: y = -7x + 8
4x+9 = 7x+3 4x-7x = 3-9 -3x = -6 x = 2
7x+2-2=16-27x = 147x/7 = 14/7x = 2
7x = 3x - 12 4x=-12 x=-3